2021
DOI: 10.1016/j.psj.2021.101326
|View full text |Cite
|
Sign up to set email alerts
|

Dietary citric acid enhances growth performance, nutrient digestibility, intestinal microbiota, antioxidant status, and immunity of Japanese quails

Abstract: A total of 300 un-sexed Japanese quail chicks (1-wk-old) were randomly allotted to 5 experimental groups to study the effect of citric acid ( CA ) on performance development, carcass estimates, blood measurements, antioxidant and immune measurements, digestive enzymes, and cecum microbiology traits of growing Japanese quail. The chicks were fed a basal diet supplemented with CA (5, 10, 15, and 20 g/kg in diet) had significantly ( P < 0.05) greater live body weights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 49 publications
6
22
2
Order By: Relevance
“…Organic acids as an alternative to antibiotic growth promoters play an important role in enhancing profitability and are safe for use in poultry production ( Adil et al., 2010 ; Kamal and Ragaa, 2014 ; Fikry et al., 2021 ). The use of organic acids has demonstrated positive effects in poultry production such as sanitizing feed to prevent pathogenic microorganism infections ( Thompson and Hinton, 1997 ), improving nutrient utilization and enhancing the growth ( Tollba, 2010 ; Islam, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic acids as an alternative to antibiotic growth promoters play an important role in enhancing profitability and are safe for use in poultry production ( Adil et al., 2010 ; Kamal and Ragaa, 2014 ; Fikry et al., 2021 ). The use of organic acids has demonstrated positive effects in poultry production such as sanitizing feed to prevent pathogenic microorganism infections ( Thompson and Hinton, 1997 ), improving nutrient utilization and enhancing the growth ( Tollba, 2010 ; Islam, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Citric acid (2-hydroxy-1, 2, 3-propane-tricarboxylic acid) is a weak organic acid and a natural preservative and that is found in all animal tissues as an intermediary substance in oxidative metabolism ( Abdel-Salam et al., 2014 ). Studies showed the addition of CA in poultry diet contributed to decreasing the counts of pathogenic intestinal bacteria ( Tollba, 2010 ; Elnaggar and Abo El-Maaty, 2017 ; Fikry et al., 2021 ). Besides the antimicrobial activity, CA also reduce the pH of gastro-intestinal tract content ( Nourmohammadi et al., 2011 ; Fikry et al., 2021 ), improve the morphometry of small intestine ( Nourmohammadi and Afzali, 2013 ), and enhance the feed nutrients digestibility ( Nourmohammadi et al., 2012 ; Fikry et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic acids and their salts are allowed in chicken diets by the European Union since they are safe and boost performance ( Ismail et al, 2020 ; Fikry et al, 2021 ; Pirzado et al, 2021 ). In broiler chicks fed a feed enriched with 1% fumaric acid, Pirgozliev et al.…”
Section: Introdutionmentioning
confidence: 99%
“…Addition of tryptophan plus CA+SS increased body weight by 13.36 and 7.07% compared to LP and control diets , respectively .On the other hand, the synergist between CA and other feed additives may be due to its effect on digestion of nutrients under low protein digestion or its effect of phosphorus utilization . Fikry et al (2021) found that adding citric acid to broilers fed significantly improved (P < 0.05) digestion coefficients of crude protein, ether extract, crude fiber, and nitrogen free extract as well as metabolizable energy compared to the control. Rafacz-Livingston et al (2005) obtained that supplementation citric acid to crossbred and commercial broiler chickens fed improved phytate phosphorus utilization in both breeds.…”
Section: Methodsmentioning
confidence: 93%